Experiences of ESL students and instructors using Grammarly in academic writing - Yueh Yea Lo (Studies in English Language and Education, 2025)
Incorporating artificial intelligence writing assistants (AIWAs) into academic writing provides opportunities to improve higher educational formative assessment. The current study seeks to examine the effectiveness of Grammarly, an AI writing assistant (AIWA), in providing instantaneous and personalised feedback to English as a second language (ESL) graduate students. The data were collected through semi-structured interviews and focus group discussions with 30 graduate students and five writing instructors with more than three years of teaching experience in graduate writing at a Malaysian public university. The results demonstrated that Grammarly enhanced student motivation, engagement, and writing proficiency through constant and detailed feedback compared to conventional approaches with time constraints and high subjectivity. However, the findings also highlighted limitations in the variety of feedback provided by Grammarly particularly in addressing nuanced academic writing needs and tailoring suggestions for complex content. Furthermore, Grammarly can support self-regulated learning while decreasing writing anxiety. This finding contributes to the ongoing discourse on AI incorporation in education and employing a balanced method in incorporating AI feedback with human oversights. This limitation underscores the importance of using Grammarly as a complementary tool rather than a standalone solution. Summarily, incorporating AIWAs responsibly can assist in providing a more conducive learning context for students future academic and professional endeavours.